Speculating on Home Improvements - CHOI, Hyun Soo (Institutional Knowledge at Singapore Management University, 2014)
We develop a speculation-based theory of home improvements. Housing services are produced from a mix of land and structures. Homeowners have an option to increase their structures (i.e. make improvements) holding fixed their land. Speculative improvements arise because overconfident homeowners mistakenly believe they can add to structures for a lower cost than a competitive construction industry. Improvements are increasing and convex in home prices. There is excessive home remodeling in equilibrium. And the change in the recoup ratio (the ratio of resale value of improvements to construction costs) is negatively correlated with construction cost growth controlling for home price appreciation. We provide evidence consistent with our theory using data on the costs and recoup values of remodeling projects across U.S. cities.